1971
DOI: 10.1055/s-0028-1094164
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β-Cell Function and Content of 6-Phosphogluconate

Abstract: Pancreatic islets from obese-hyperglycemic mice were used for studying a proposed relationship between insulin release and the ß.cell content of 6-phosphogluconate. A short period of ischemia reduced the amount of this intermediate in the islets but not in the exocrine pancreas. There was a steep rise of 6-phosphogluconate in microdissected islets when the extracellular glucose concentration was increased from 0.6 to 3.0 mg/m1. A plateau of about 40 J.II1loles 6-phosphogluconate per kg islet dry weight was rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1971
1971
1984
1984

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…With 6-phosphogluconate content exactly the converse is true; there is no rise in 6-phosphogluconate in the fed state but almost a three-fold increase in the starved state. This lack of correlation of 6-phosphogluconate concentration with insulin release agrees with the results of Idahl et al (1971), who showed that the addition of adrenaline to or omission of Ca2+ from a high-glucose medium (both experimental conditions that inhibit insulin release) gave a significant elevation of the islet 6-phosphogluconate content.…”
Section: Discussionsupporting
confidence: 90%
“…With 6-phosphogluconate content exactly the converse is true; there is no rise in 6-phosphogluconate in the fed state but almost a three-fold increase in the starved state. This lack of correlation of 6-phosphogluconate concentration with insulin release agrees with the results of Idahl et al (1971), who showed that the addition of adrenaline to or omission of Ca2+ from a high-glucose medium (both experimental conditions that inhibit insulin release) gave a significant elevation of the islet 6-phosphogluconate content.…”
Section: Discussionsupporting
confidence: 90%
“…The curve relating glucose-utilization rate to glucose concentration was similar in shape to those described for a number of other glucose-sensitive parameters 1972 of islets, e.g. glucose oxidation rate and islet glucose 6-phosphate concentration , insulin release (Malaisse et al, 1967), islet 6-phosphogluconate concentration (Montague & Taylor, 1970;Idahl et al, 1971) and the incidence of fl-cell membrane action potentials (Dean & Matthews, 1970). The only other published values for the rate of glucose utilization by mammalian islets are those of Snyder et al (1970), who measured glucose uptake by isolated rat islets at 3.3 and 16.7mM extracellular glucose: the rates of 25 and 130pmol/h per islet calculable from their results are comparable with the rates of 19 and 89pmol/h per islet at these two glucose concentrations obtained in the present study (Fig.…”
Section: Glucose Utilization By Mouse Isletssupporting
confidence: 61%
“…Previous use of this nucleotide in the same experimental system induced a significant decrease in the amount of glycogen but no alteration in the levels of fructose-1,6-diphosphate or 6-phosphogluconate [Hellman, 1970b;Idahl and Hellman, 1971;. These results might indicate that the effect of dibutyryl cyclic 3,5-AMP on the carbohydrate metabolism of the /9-cells is essentially restricted to glycogen turnover.…”
Section: Discussionmentioning
confidence: 48%